High eosinophil blood counts are associated with a shorter length of hospital stay in exacerbated COPD patients – a retrospective analysis - Timm Greulich; Julia Tüffers; Sina Mager; Anna Eder; Michael Maxheim; Peter Alter; Bernd Schmeck; Claus F. Vogelmeier (Respiratory Research, 2020)
Abstract Background In COPD, the course of the disease including morbidity and mortality is strongly associated with severe exacerbations. The current GOLD recommendations emphasize blood eosinophil counts as a marker for responsiveness to inhaled corticosteroids (ICS). Retrospective analyses from randomized clinical trials indicate a favorable response to systemic corticosteroids in exacerbated COPD patients with blood eosinophils > 2%, however data outside clinical trials are scarce. Patients and methods We retrospectively evaluated data from 1007 cases of patients who were admitted to the University Medical Center Marburg between 01/2013 and 12/2018. All patients had been diagnosed with an acute exacerbation of COPD (ICD-10 J44.0/J44.1). Our analysis was based on a subgroup of 417 patients in whom a full blood cell count was obtained at the day of admission. Patients were predominantly male (63.3%), had a median age of 74 years (IQR 65 years – 83 years) and a median FEV1 of 1.03 l (42.6% predicted). We compared the hospital length of stay and other outcome parameters using established thresholds for the eosinophil blood cell count (100 and 300 eosinophils/μl and 2%). Results Patients with low eosinophils (< 2%, <100 cells/μl) had a longer median time in hospital (length of hospital stay – LOS) as compared to patients with high eosinophils (< 2%: 9.31 vs. ≥2%:7 days, and < 100/μl: 10 vs. 100–300/μl: 8 vs. > 300/μl: 7 days). The median CRP was higher in patients with low eosinophils as compared to the other groups (< 2%: 22.7 vs. ≥2%: 9 mg/dl and < 100: 25 vs. 100–300: 13.5 vs. > 300: 7.1 mg/dl). Time to re-hospitalization or time to death did not differ between strata of eosinophils. Sensitivity analysis in a subgroup of patients in which pneumonia was excluded by chest x-ray did not significantly alter the results. Conclusion The results support the hypothesis that patients with severe COPD exacerbations and elevated blood eosinophil counts respond better to systemic corticosteroid treatment than patients with a non-eosinophilic exacerbation.